TRANSFORMATION AND CONTRADICTIONS OF THE IDENTITY POLITICS IN MODERN WESTERN SOCIAL AND POLITICAL IDEOLOGY AND PRACTICE OF THE CIVIL SOCIETY - S. P. Mitrakhovich (Publishing House of the State University of Management, 2020)
Identity politics has become a crucial feature of the transformation of modern social and political relations in many countries around the world. Representatives of “progressive” structures actively engaged in such a struggle, trying to undermine the foundations of the existing conservative social system and the established balance of institutions and relative powers of actors. Largely initiated by civil society organizations representing social minorities, this policy has become an instrument for the realization of the tasks of the state power. At the same time, identity politics, showing disparity approach to various social groups, while demanding the increasing powers of the State in its implementation, remains deeply contradictory and generates ideological hybrids such as “eco-authoritarianism” or “liberal authoritarianism”.